Negative electrode, lithium-ion secondary battery, and lithium-ion secondary battery module
Patent Information
- Application Number
- JP2025058187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明によれば、エネルギー密度およびサイクル特性の性能バランスが向上したリチウムイオン二次電池を得ることが可能な負極、並びに、エネルギー密度量およびサイクル特性の性能バランスが向上したリチウムイオン二次電池およびリチウムイオン二次電池モジュールを提供することができる。
Smart Images

Figure 2026165677000002 
Figure 2026165677000001
Abstract
Description
[Technical Field]
[0001] This invention relates to a negative electrode, a lithium-ion secondary battery, and a lithium-ion secondary battery module. [Background technology]
[0002] Carbon-based and silicon-based active materials are known as negative electrode active materials for lithium-ion secondary batteries. Silicon-based active materials are attracting attention because they can produce lithium-ion secondary batteries with higher capacity compared to those using carbon-based active materials. An example of a lithium-ion secondary battery technology using a silicon-based active material as the negative electrode active material is the one described in Patent Document 1.
[0003] Patent Document 1 describes a particulate material consisting of a plurality of composite particles, wherein the composite particles are (a) a porous carbon skeleton including micropores and mesopores, and the total pore volume P of the micropores and mesopores is measured by gas adsorption. 1 cm 3 / g has P 1 This represents a number with a value between 0.5 and 1.5, and PD 90 The pore diameter is at least 3 nm and less than 12 nm, P 1 A particulate material is described having (b) a porous carbon skeleton with a micropore volume ratio of 0.43 to 0.85, and (b) a plurality of nanoscale elemental silicon domains arranged within the pores of the porous carbon skeleton, wherein the particulate material contains 25 to 65 mass% silicon, and at least 20 mass% of the silicon is surface silicon measured by thermogravimetric analysis (TGA). Patent Document 1 describes that the particulate material has a large electrochemical capacity, low overall expansion, and comparable reversible capacity retention, thereby enabling high-capacity electroactive material filling. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Unexamined Patent Publication (National Publication of Translated Version) No. 2023-517052 [Summary of Invention] [Problem to be Solved by the Invention]
[0005] A lithium ion secondary battery using a silicon-based active material as the negative electrode active material has a large expansion and contraction of the silicon-based active material during charge and discharge, and thus there is room for improvement in cycle characteristics compared to a lithium ion secondary battery using a carbon-based active material as the negative electrode active material.
[0006] The present invention provides a negative electrode capable of obtaining a lithium ion secondary battery with an improved performance balance between energy density and cycle characteristics, as well as a lithium ion secondary battery and a lithium ion secondary battery module with an improved performance balance between energy density and cycle characteristics. [Means for Solving the Problem]
[0007] The present inventors have conducted extensive and intensive studies to achieve the above problem. As a result, the present inventors have found that a lithium ion secondary battery with an improved performance balance between energy density and cycle characteristics can be obtained by using a negative electrode comprising graphite powder and Si / C powder containing Si-C composite particles in which the area ratio of particles having a specific particle diameter falls within a predetermined range, and have completed the present invention.
[0008] According to the present invention, the following negative electrode, lithium ion secondary battery, and lithium ion secondary battery module are provided.
[0009] [1] A negative electrode comprising a negative electrode active material layer containing a negative electrode active material and a binder, wherein the negative electrode active material comprises graphite powder and Si / C powder containing Si-C composite particles, the negative electrode, wherein the area ratio Y measured by the following (Method 1) is 25 area% or less. (Method 1) Observation of the Si-C composite particles in the negative electrode active material layer is performed using STEM-HAADF (Scanning Transmission Electron Microscope - High-Angle Scattering Annular Dark-Field Spectroscopy) under conditions of a magnification of 1,000,000x and an acceleration voltage of 200kV, and a STEM-HAADF image of the Si-C composite particles is obtained. Next, using image analysis software, the total area S1 of the Si-C composite particles and the total area S2 of Si particles X whose projected area circle equivalent diameter calculated from the area value of each Si particle in the Si-C composite particles is between 10 nm and 200 nm are calculated from the STEM-HAADF image. Next, the area ratio Y1 (=100 × S2 / S1) is calculated from the obtained S1 and S2. The average value of the area ratio Y1 of any 10 Si-C composite particles is taken as the area ratio Y. [2] The negative electrode according to [1], wherein the content of the graphite powder in the negative electrode active material is 25.0 parts by mass or more and 99.0 parts by mass or less, when the total amount of the negative electrode active material is 100.0 parts by mass. [3] The negative electrode according to [1] or [2], wherein the content of the Si / C powder in the negative electrode active material is 1.0 part by mass or more and 75.0 parts by mass or less when the total amount of the negative electrode active material is 100.0 parts by mass. [4] Median diameter D in the volume frequency particle size distribution of the aforementioned graphite powder as determined by laser diffraction scattering. 50 A negative electrode as described in any of [1] to [3], wherein the diameter is 1.0 μm or more and 30.0 μm or less. [5] Median diameter D in the volume frequency particle size distribution of the Si / C powder obtained by laser diffraction scattering method. 50 A negative electrode as described in any of [1] to [4], wherein the diameter is 1.0 μm or more and 20.0 μm or less. [6] The negative electrode according to any one of [1] to [5], wherein the binder comprises a polycarboxylic acid polymer. [7] The negative electrode according to [6], wherein the polycarboxylic acid polymer comprises an alkali metal salt of a polycarboxylic acid. [8] The negative electrode according to any one of [1] to [7], wherein the content of the binder in the negative electrode active material layer is 1.0 part by mass or more and 10.0 parts by mass or less when the total amount of the negative electrode active material layer is 100 parts by mass. [9] The negative electrode according to any one of [1] to [8], further comprising a conductive additive in the negative electrode active material layer.
[10] The negative electrode according to [9], wherein the content of the conductive additive in the negative electrode active material layer is 0.01 parts by mass or more and 2 parts by mass or less when the total amount of the negative electrode active material layer is 100 parts by mass.
[11] The negative electrode according to [9] or
[10] , comprising a carbon material as the conductive additive.
[12] The negative electrode according to any one of [9] to
[11] , comprising a conductive additive carbon nanotube.
[13] The density of the negative electrode active material layer is 0.70 g / cm³. 3 The negative electrode is as described in any of [1] to
[12] above.
[14] A lithium-ion secondary battery having a negative electrode as described in any of [1] to
[13] .
[15] A lithium-ion secondary battery as described in
[14] , having an energy density of 725 Wh / L or more on a cell basis.
[16] A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in
[14] or
[15] . [Effects of the Invention]
[0010] According to the present invention, it is possible to provide a negative electrode that can obtain a lithium-ion secondary battery with an improved performance balance between energy density and cycle characteristics, as well as a lithium-ion secondary battery and a lithium-ion secondary battery module with an improved performance balance between energy density and cycle characteristics. [Brief explanation of the drawing]
[0011] [Figure 1]This is a schematic cross-sectional view illustrating an example of a lithium-ion secondary battery according to this embodiment. [Modes for carrying out the invention]
[0012] Embodiments of the present invention will be described below with reference to the drawings. In all drawings, similar components are denoted by the same reference numeral, and explanations are omitted where appropriate. Furthermore, the drawings are schematic and do not necessarily correspond to actual dimensional proportions. In the specification, unless otherwise specified, the notation "A to B" regarding a numerical range means A or greater and B or less. For example, 1 to 5% means 1% or greater and 5% or less.
[0013] <Negative electrode> The negative electrode of this embodiment is a negative electrode comprising a negative electrode active material layer containing a negative electrode active material and a binder, wherein the negative electrode active material contains graphite powder and Si / C powder containing Si-C composite particles, and the area ratio Y, measured by the following (Method 1), is 25 area% or less. (Method 1) Observation of the Si-C composite particles in the negative electrode active material layer is performed using STEM-HAADF (Scanning Transmission Electron Microscope - High-Angle Scattering Annular Dark-Field Spectroscopy) under conditions of a magnification of 1,000,000x and an acceleration voltage of 200kV, and a STEM-HAADF image of the Si-C composite particles is obtained. Next, using image analysis software, the total area S1 of the Si-C composite particles and the total area S2 of Si particles X whose projected area circle equivalent diameter calculated from the area value of each Si particle in the Si-C composite particles is between 10 nm and 200 nm are calculated from the STEM-HAADF image. Next, the area ratio Y1 (=100 × S2 / S1) is calculated from the obtained S1 and S2. The average value of the area ratio Y1 of any 10 Si-C composite particles is taken as the area ratio Y. By having the above configuration, the negative electrode of this embodiment can improve the performance balance between energy density and cycle characteristics of the resulting lithium-ion secondary battery.
[0014] The mechanism by which the negative electrode of this embodiment provides the above effect is not clear, but the following reasons are possible. First, the negative electrode in this embodiment contains high-capacity Si-C composite particles as the negative electrode active material. This is expected to improve the energy density of the resulting lithium-ion secondary battery. Furthermore, the inventors hypothesized that in the manufacturing process of a negative electrode active material layer containing graphite powder and Si / C powder, relatively large Si particles contained in the Si / C powder adhere to the surface of the graphite powder and Si-C composite particles, resulting in a decrease in the energy density and cycle characteristics of the resulting lithium-ion secondary battery. Based on the above inference, the inventors conducted further intensive studies and found that there is a correlation between the area ratio Y in the negative electrode active material layer and the cycle density of the resulting lithium-ion secondary battery. A small area ratio Y suggests that the proportion of relatively large Si particles adhering to the surface of the graphite powder and Si-C composite particles is low. If the proportion of relatively large Si particles is high, it is thought that the newly formed surfaces created by the cracking of these relatively large Si particles react with the electrolyte, leading to a decrease in the battery's cycle performance. On the other hand, in this embodiment, since the area ratio Y in the negative electrode active material layer is less than or equal to the above upper limit, the amount of relatively large Si particles in the negative electrode active material layer is suppressed, and as a result, it is thought that the cycle characteristics can be improved. For the reasons stated above, it is believed that the negative electrode of this embodiment can improve the performance balance between energy density and cycle characteristics of the resulting lithium-ion secondary battery.
[0015] The area ratio Y of the negative electrode active material layer of the present embodiment is 25 area% or less, preferably 22 area% or less, more preferably 20 area% or less, further preferably 15 area% or less, still further preferably 10 area% or less, and even more preferably 5 area% or less, from the viewpoint of improving the performance balance between the energy density and cycle characteristics of the obtained lithium ion secondary battery. In addition, the lower limit value of the area ratio Y of the negative electrode active material layer of the present embodiment is not particularly limited, and may be, for example, 0.1 area% or more, 0.5 area% or more, or 0.8 area% or more. The area ratio Y of the negative electrode active material layer of the present embodiment may be 0.1 area% or more and 25 area% or less, 0.1 area% or more and 22 area% or less, 0.1 area% or more and 20 area% or less, 0.1 area% or more and 15 area% or less, 0.5 area% or more and 10 area% or less, or 0.8 area% or more and 5 area% or less, from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the obtained lithium ion secondary battery. The area ratio Y of the negative electrode active material layer of the present embodiment can be adjusted by adjusting the type, blending ratio, and the like of each component constituting the negative electrode active material layer. In particular, the heat treatment conditions when producing the Si / C powder, the blending amount of the Si / C powder, and the like are important.
[0016] The median diameter D in the volume frequency particle size distribution of the Si / C powder of the present embodiment obtained by the laser diffraction scattering method 50 is preferably 1.0 μm or more and 20.0 μm or less, more preferably 2.0 μm or more and 15.0 μm or less, and further preferably 3.0 μm or more and 10.0 μm or less, from the viewpoint of further improving the cycle characteristics of the obtained lithium ion secondary battery.
[0017] In the present embodiment, examples of the method for measuring the volume frequency particle size distribution of the Si / C powder include the following methods. First, the Si / C powder is suspended in a dispersion medium and dispersed using ultrasonic waves. Next, the volume frequency particle size distribution of the Si-C composite particles is measured using a laser diffraction particle size distribution analyzer by laser diffraction scattering. The measurement is performed five times, and the arithmetic mean of the obtained values can be used.
[0018] In this embodiment, the method for producing Si / C powder is not particularly limited, but for example, a median diameter of 4.0 to 10.0 μm and a specific surface area of 1600 to 1800 m² are used. 2 Si / C powder can be obtained by a manufacturing method in which a porous carbon material of / g is placed in a tubular furnace, the inside of the tubular furnace is replaced with argon gas, a mixed gas of silane gas and nitrogen gas with 1-3 mol% silane gas is flowed into the tubular furnace at a flow rate of 250-350 sccm, and the process is carried out by maintaining the conditions of heating temperature of 450-650°C, 700-800 Torr, and heating time of 90-250 minutes (hereinafter also referred to as the heat treatment process). Furthermore, in the method for producing Si / C powder, the area ratio Y of the negative electrode active material layer can be adjusted by changing the conditions of the heat treatment process, and in particular there is a correlation between the increase or decrease in heating temperature and heating time in the heat treatment process and the area ratio Y, with the area ratio Y tending to increase as heat is added. For example, when the heating temperature is 450°C or higher and 580°C or lower, the heating time is preferably 110 minutes or higher and 250 minutes or lower, and when the heating temperature is above 580°C and 650°C or lower, the heating time is preferably 90 minutes or higher and 150 minutes or lower.
[0019] From the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery, the Si / C powder content in the negative electrode active material of this embodiment is preferably 1.0 parts by mass or more and 75.0 parts by mass or less, more preferably 3.0 parts by mass or more and 70.0 parts by mass or less, even more preferably 5.0 parts by mass or more and 65.0 parts by mass or less, even more preferably 10.0 parts by mass or more and 60.0 parts by mass or less, and even more preferably 12.0 parts by mass or more and 55.0 parts by mass or less, when the total amount of the negative electrode active material is 100.0 parts by mass.
[0020] In this embodiment, the graphite powder is preferably graphite powder containing amorphous carbon on its surface, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery. Furthermore, it is preferable to use a combination of graphite powder containing amorphous carbon on its surface and graphite powder that does not contain amorphous carbon on its surface.
[0021] Furthermore, when using a combination of graphite powder containing amorphous carbon on its surface and graphite powder not containing amorphous carbon on its surface as the graphite powder, the content M of the graphite powder containing amorphous carbon on its surface in the negative electrode active material layer of this embodiment is A The content of graphite powder that does not contain amorphous carbon on its surface relative to M B The mass ratio (M B / M A From the viewpoint of further improving the cycle characteristics of the resulting lithium-ion secondary battery, the coefficient of
[0022] Median diameter D in the volume frequency particle size distribution of graphite powder according to the laser diffraction scattering method of this embodiment 50 From the viewpoint of further improving the energy density of the resulting lithium-ion secondary battery, the particle size is preferably 1.0 μm to 30.0 μm, more preferably 3.0 μm to 25.0 μm, and even more preferably 5.0 μm to 20.0 μm.
[0023] From the viewpoint of further improving the cycle characteristics of the resulting lithium-ion secondary battery, the amount of graphite powder in the negative electrode active material of this embodiment is preferably 25.0 parts by mass or more and 99.0 parts by mass or less, more preferably 30.0 parts by mass or more and 97.0 parts by mass or less, even more preferably 35.0 parts by mass or more and 95.0 parts by mass or less, even more preferably 40.0 parts by mass or more and 90.0 parts by mass or less, and even more preferably 45.0 parts by mass or more and 88.0 parts by mass or less, when the total amount of the negative electrode active material is 100.0 parts by mass.
[0024] Examples of binders in the negative electrode active material layer of this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); polycarboxylic acid polymers such as poly(meth)acrylic acid; conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination. Among these, the binder in the negative electrode active material layer of this embodiment preferably comprises one or more selected from the group consisting of fluororesin, polycarboxylic acid polymer, and synthetic rubber, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, and more preferably comprises one or more selected from the group consisting of polyvinylidene fluoride, polycarboxylic acid polymer, and styrene-butadiene rubber.
[0025] The binder content in the negative electrode active material layer of this embodiment is preferably 1.0 part by mass or more and 10.0 parts by mass or less, more preferably 1.5 parts by mass or more and 8.0 parts by mass or less, even more preferably 1.5 parts by mass or more and 6.0 parts by mass or less, and even more preferably 2.0 parts by mass or more and 4.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100 parts by mass.
[0026] The binder included in the negative electrode active material layer of this embodiment preferably includes a polycarboxylic acid polymer, from the viewpoint of further improving the cycle characteristics of the resulting lithium-ion secondary battery. In this specification, a polycarboxylic acid polymer means a polymer containing an unsaturated carboxylic acid or a salt thereof as a monomer unit. Examples of unsaturated carboxylic acids or salts thereof include acrylic acid or a salt thereof, methacrylic acid or a salt thereof, maleic acid or a salt thereof, fumaric acid or a salt thereof, and among these, preferably one or more selected from the group consisting of acrylic acid or a salt thereof and methacrylic acid or a salt thereof, more preferably containing acrylic acid or a salt thereof, and even more preferably containing acrylic acid. Furthermore, regarding the salt, alkali metal salts (e.g., Li, Na, K, etc.) are preferred, lithium salts or sodium salts are more preferred, and lithium salts are even more preferred. The polycarboxylic acid polymer of this embodiment preferably comprises an alkali metal salt of a polycarboxylic acid, more preferably one or more selected from the group consisting of alkali metal salts of polyacrylic acid and alkali metal salts of polymethacrylic acid, more preferably an alkali metal salt of polyacrylic acid, and even more preferably a lithium salt or sodium salt of polyacrylic acid, and preferably a lithium salt of polyacrylic acid from the viewpoint of further improving the cycle characteristics of the resulting lithium-ion secondary battery.
[0027] In the negative electrode of this embodiment, the negative electrode active material layer preferably further includes a conductive additive from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery.
[0028] Examples of conductive additives in the negative electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon black such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination. Among these, the conductive additive in the negative electrode active material layer of this embodiment preferably contains carbon materials, more preferably carbon nanotubes, and even more preferably single-walled carbon nanotubes, from the viewpoint of further improving the performance balance between the energy density and cycle characteristics of the resulting lithium-ion secondary battery.
[0029] From the viewpoint of further improving the balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery, the content of the conductive additive in the negative electrode active material layer of this embodiment is preferably 0.01 parts by mass or more and 2.0 parts by mass or less, more preferably 0.02 parts by mass or more and 1.5 parts by mass or less, even more preferably 0.03 parts by mass or more and 1.0 part by mass or less, even more preferably 0.05 parts by mass or more and 0.8 parts by mass or less, and even more preferably 0.08 parts by mass or more and 0.5 parts by mass or less, when the total amount of the negative electrode active material layer is 100 parts by mass.
[0030] The specific surface area of the carbon nanotubes in the negative electrode active material layer of this embodiment, as measured by the nitrogen adsorption BET method, is preferably 300 m², from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery. 2 / g or more, more comfortably 350m 2 / g or more, more preferably 400m 2 / g or more, more preferably 450m 2 / g or more, more preferably 500m 2 It is 1 / g or more. There is no particular limit to the upper limit of the specific surface area of carbon nanotubes in the negative electrode active material layer of this embodiment, but for example, 2500m 2 It may be less than / g, and 2200m 2 It may be less than / g, and 2000m 2 It may be less than / g. From the viewpoint of further improving the performance balance between energy density and cycle characteristics of the resulting lithium-ion secondary battery, the specific surface area of the carbon nanotubes in the negative electrode active material layer of this embodiment is preferably 300 m². 2 / g or more 2500m 2 / g or less, more preferably 350m 2 / g or more 2200m 2 / g or less, more preferably 400m 2 / g or more 2000m 2 / g or less, more preferably 450m 2 / g or more 2000m 2 / g or less, more preferably 500m 2 / g or more 2000m 2 It is less than / g. The specific surface area of carbon nanotubes can be measured by the method described in the examples.
[0031] The aspect ratio of the carbon nanotubes in this embodiment is preferably 100 or more, more preferably 250 or more, even more preferably 500 or more, even more preferably 750 or more, and even more preferably 1000 or more, from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery. There is no particular upper limit to the aspect ratio of the carbon nanotubes in this embodiment, but it may be, for example, 100,000 or less, 50,000 or less, 20,000 or less, 10,000 or less, or 7,500 or less. The aspect ratio of the carbon nanotubes in this embodiment is preferably 100 to 100,000, more preferably 250 to 50,000, even more preferably 500 to 20,000, even more preferably 750 to 10,000, and even more preferably 1,000 to 7,500, from the viewpoint of further improving the performance balance of energy density and cycle characteristics of the resulting lithium-ion secondary battery.
[0032] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the thickness of the negative electrode active material layer in this embodiment is preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, and even more preferably 50 μm to 150 μm.
[0033] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the density of the negative electrode active material layer in this embodiment is preferably 0.70 g / cm³. 3 More than 3.00g / cm 3 More preferably, 1.00 g / cm³ 3 More than 2.50g / cm 3 More preferably, 1.30 g / cm³ 3 More than 2.00g / cm 3 More preferably, 1.40 g / cm³ 3 More than 1.80g / cm 3 The following applies:
[0034] The negative electrode current collector in this embodiment may be made of, for example, copper, stainless steel, nickel, titanium, or an alloy thereof. The shape of the negative electrode current collector may be, for example, foil, a flat plate, or a mesh. The thickness of the negative electrode current collector is not particularly limited, but is, for example, 1 μm or more and 50 μm or less.
[0035] <Lithium-ion rechargeable battery> The lithium-ion secondary battery of this embodiment is equipped with the negative electrode of this embodiment. Because the lithium-ion secondary battery of this embodiment is equipped with the negative electrode of this embodiment, the performance balance between energy density and cycle characteristics is improved.
[0036] The lithium-ion secondary battery of this embodiment will be described with reference to the figures. Figure 1 is a schematic cross-sectional view showing an example of the lithium-ion secondary battery of this embodiment. As shown in Figure 1, the lithium-ion secondary battery 10 comprises the negative electrode, electrolyte, and positive electrode of this embodiment. A separator 5 can also be provided between the positive electrode and the negative electrode. Multiple pairs of positive and negative electrodes can be provided.
[0037] The lithium-ion secondary battery 10 has a positive electrode comprising a positive electrode current collector 3 made of a metal such as aluminum foil and a positive electrode active material layer 1 containing a positive electrode active material provided thereon, and a negative electrode comprising a negative electrode current collector 4 made of a metal such as copper foil and a negative electrode active material layer 2 containing a negative electrode active material provided thereon. The positive electrode and the negative electrode are laminated via a separator 5 made of a nonwoven fabric or a polypropylene microporous film, for example, so that the positive electrode active material layer 1 and the negative electrode active material layer 2 face each other. This electrode pair is housed in a container formed of an outer casing 6, 7 made of an aluminum laminate film, for example. A positive electrode tab 9 is connected to the positive electrode current collector 3 and a negative electrode tab 8 is connected to the negative electrode current collector 4, and these tabs are led out of the container. An electrolyte is injected into the container and sealed. A structure in which a group of electrodes, each consisting of multiple laminated electrode pairs, is housed in the container is also possible.
[0038] The lithium-ion secondary battery 10 can be manufactured according to known methods. For electrodes, for example, laminates or wound bodies can be used. For the outer casing, metal casings or aluminum laminate casings can be used as appropriate. The shape of the battery may be any shape, such as coin type, button type, sheet type, cylindrical type, prismatic type, or flat type.
[0039] In the lithium-ion secondary battery of this embodiment, the positive electrode preferably comprises a positive electrode active material layer containing a positive electrode active material and a positive electrode current collector. The positive electrode active material layer of this embodiment preferably comprises a positive electrode active material and a binder, and more preferably comprises a positive electrode active material, a binder and a conductive additive.
[0040] The positive electrode active material in the positive electrode active material layer of this embodiment may be, for example, lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-cobalt-manganese-aluminum composite oxide, and other composite oxides of lithium and transition metals; transition metal sulfides such as TiS2, FeS, MoS2; and MnO, V2O5, V6O 13 Examples include transition metal oxides such as TiO2, and olivine-type lithium phosphate oxides. One of these may be used alone, or two or more may be used in combination.
[0041] Examples of conductive additives in the positive electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjenblack; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination.
[0042] Examples of binders in the positive electrode active material layer of this embodiment include fluorine-based binders such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF); and aqueous binders such as styrene-butadiene rubber. One of these may be used alone, or two or more may be used in combination.
[0043] The positive electrode current collector of this embodiment may be made of, for example, aluminum, stainless steel, nickel, titanium, or an alloy thereof. The shape of the positive electrode current collector may be, for example, foil, a flat plate, or a mesh. The thickness of the positive electrode current collector is not particularly limited, but for example, it is 1 μm or more and 50 μm or less.
[0044] Examples of electrolytes in this embodiment include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), and butylene carbonate (BC); linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC); aliphatic carboxylic acid esters; γ-lactones such as γ-butyrolactone; linear ethers; and cyclic ethers, in which lithium salts such as lithium hexafluoride phosphate (LiPF6), lithium borofluoride (LiBF4), LiFSI, and lithium perchlorate (LiClO4) are dissolved. The organic solvent may be used alone or in combination of two or more.
[0045] The separator of this embodiment is, for example, mainly made of a porous membrane, woven fabric, nonwoven fabric, etc., and as the resin component, for example, polyolefin resins such as polypropylene and polyethylene, polyester resins, acrylic resins, styrene resins, or nylon resins can be used. In addition, if necessary, a layer containing inorganic particles may be formed in the separator, and examples of inorganic particles include insulating oxides, nitrides, sulfides, carbides, etc.
[0046] As the outer casing of this embodiment, for example, a case or can made of a flexible film can be used, and from the viewpoint of reducing the weight of the battery, it is preferable to use a flexible film. The flexible film can be one in which a resin layer is provided on both the front and back surfaces of a metal base layer. The metal layer can be selected to have barrier properties such as preventing leakage of electrolyte and intrusion of moisture from the outside, and can be made of aluminum, stainless steel, etc. A heat-sealable resin layer, such as a modified polyolefin, is provided on at least one surface of the metal layer. The outer casing is formed by facing the heat-sealable resin layers of the flexible film toward each other and heat-sealing the area around the part that houses the electrode laminate. A resin layer such as a nylon film or polyester film can be provided on the surface of the outer casing opposite to the surface on which the heat-sealable resin layer is formed.
[0047] The energy density of the lithium-ion secondary battery of this embodiment is preferably 725 Wh / L or more, more preferably 728 Wh / L or more, even more preferably 730 Wh / L or more, even more preferably 733 Wh / L or more, and even more preferably 735 Wh / L or more, on a cell basis. The upper limit of the energy density of the lithium-ion secondary battery of this embodiment is not particularly limited, but for example it may be 1500 Wh / L or less, 1200 Wh / L or less, 1000 Wh / L or less, or 950 Wh / L or less. The energy density of the lithium-ion secondary battery in this embodiment, on a cell basis, can be measured, for example, by the method 1 described below. (Method 1) In this embodiment, the lithium-ion secondary battery is charged at 7.2mA, and after the upper voltage limit reaches 4.2V, it is charged at a constant voltage until the total charging time is 12 hours. Next, it is discharged at a constant current of 7.2mA until the lower voltage limit reaches 2.5V. Then, it is charged again under the same conditions, left in a constant temperature bath at 45°C for 3 days, discharged again under the same conditions, and then charged and discharged one more time. At this time, the capacity and average voltage at the time of the final discharge are measured. Next, after the final discharge, the thickness of the lithium-ion secondary battery is measured. Then, based on the above measurements, the electrode area of the electrode stack, the thickness of the laminate casing, the thickness of the negative electrode current collector, and the thickness of the positive electrode current collector in the positive electrode, the cell-equivalent energy density (Wh / L) is calculated using the following formula. (Energy density) = (Capacity at the end of discharge) × (Average voltage at the end of discharge) / (Electrode area of the electrode stack) / ((Thickness of lithium-ion secondary battery) - (Thickness of laminate casing) - (Thickness of positive electrode current collector) / 2 - (Thickness of negative electrode current collector) / 2)
[0048] The capacity retention rate of the lithium-ion secondary battery of this embodiment, as measured by the following method (Method 2), is preferably 86.0% or higher, more preferably 86.5% or higher, even more preferably 87.0% or higher, even more preferably 87.5% or higher, and even more preferably 88.0% or higher. The upper limit of the capacity retention rate of the lithium-ion secondary battery according to the following (Method 2) of this embodiment is not particularly limited, but may be, for example, 100.0% or less, 98.0% or less, or 95.0% or less. (Method 2) The lithium-ion secondary battery of this embodiment is placed in a constant temperature bath at 45°C and charged at 30mA. After the upper limit voltage reaches 4.2V, it is charged at a constant voltage until the total charging time is 2.5 hours. Next, it is discharged at a constant current of 30mA until the lower limit voltage reaches 2.5V. Then, this charge-discharge cycle is repeated 500 times, and the ratio of the discharge capacity after 500 cycles to the discharge capacity after 1 cycle is calculated and defined as the capacity retention rate (%).
[0049] <Lithium-ion secondary battery module> The lithium-ion secondary battery module of this embodiment comprises the lithium-ion secondary battery of this embodiment. Since the lithium-ion secondary battery of this embodiment has an improved balance of energy density and cycle characteristics, the lithium-ion secondary battery module of this embodiment also has an improved balance of energy density and cycle characteristics.
[0050] The lithium-ion secondary battery module of this embodiment preferably includes two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes a housing capable of housing two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes one or more selected from the group consisting of a protection circuit to protect the lithium-ion secondary batteries from overcurrent, a balance circuit to equalize the voltage between the electrodes of the lithium-ion secondary batteries, a controller to control the lithium-ion secondary batteries, a cooler capable of cooling the lithium-ion secondary batteries, and a heater capable of heating the lithium-ion secondary batteries.
[0051] The lithium-ion secondary battery module of this embodiment can be used in a battery system comprising multiple electrically connected lithium-ion secondary battery modules and a battery control system. Examples of battery systems include battery packs, stationary battery systems, automotive power battery systems, automotive auxiliary battery systems, and emergency power supply battery systems.
[0052] The embodiments of the present invention have been described above, but these are merely examples, and various other configurations can also be adopted.
[0053] It should be noted that the present invention is not limited to the embodiments described above, and any modifications, improvements, etc., that can achieve the objectives of the present invention are included in the present invention. [Examples]
[0054] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.
[0055] <Measurement of specific surface area of graphite powder and conductive additive> The specific surface area of graphite powder and conductive additive was measured using a fully automated specific surface area measuring device (Macsorb HM-1208, manufactured by Mountec Co., Ltd.) in accordance with JIS Z 8830:2013, employing the BET flow method and the single-point method.
[0056] <Measurement of aspect ratio (fiber length / fiber diameter) of single-walled carbon nanotubes> Using a scanning electron microscope, single-walled carbon nanotubes were observed under conditions of 5000x magnification and a field of view of 20 μm × 20 μm. The fiber diameter and fiber length of the single-walled carbon nanotubes were measured, and the aspect ratio was calculated. A total of 100 samples were measured, and the arithmetic mean values were used for each.
[0057] <Median diameter D of the negative electrode active material> 50 Measurement > From the volume frequency particle size distribution measured by the laser diffraction scattering method using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, SALD-2300), the median diameter D at which the cumulative value is 50% 50 was determined. Here, the negative electrode active material was suspended in a dispersion medium (0.1 mass% sodium hexametaphosphate aqueous solution), subjected to ultrasonic dispersion, and then measured. For each median diameter D 50 , the arithmetic mean value of 5 measured values was adopted
[0058] <Preparation of Si / C Powder 1> A porous carbon material (D 50 : 4.8 μm, specific surface area: 1678 m 2 / g) was placed in a tubular furnace, the inside of the tubular furnace was purged with argon gas, then a mixed gas of 2 mol% silane gas and 98 mol% nitrogen gas was flowed into the tubular furnace at a flow rate of 300 sccm, and heat treatment was performed by holding under conditions of 600°C, 760 Torr, and 120 minutes. Next, the product was cooled to room temperature to obtain Si / C Powder 1.
[0059] <Preparation of Si / C Powders 2 to 5> Si / C Powder 2 was produced in the same manner as the production of Si / C Powder 1, except that the heat treatment temperature was changed to 550°C. Further, Si / C Powder 3 was produced in the same manner as the production of Si / C Powder 1, except that the heat treatment temperature was changed to 550°C and the heat treatment time was changed to 240 minutes. Further, Si / C Powder 4 was produced in the same manner as the production of Si / C Powder 1, except that the heat treatment temperature was set to 500°C. Further, Si / C Powder 5 was produced in the same manner as the production of Si / C Powder 1, except that the heat treatment time was changed to 240 minutes.
[0060] Cross-sections of Si-C composite particles contained in the obtained Si / C powder were analyzed using a scanning electron microscope (Hitachi High-Tech Corporation, SU3500), an energy-dispersive X-ray spectroscopy detector (Oxford Instruments, Ultim Max 40), and image analysis software (Oxford Instruments, Aztec). Secondary electrons were selected as the detection target, and elemental mapping of silicon and carbon was performed under the conditions of an acceleration voltage of 3kV, 20 mapping integrations, and a magnification of 3000x. This confirmed that the Si-C composite particles contained silicon, and that silicon was present in at least a portion of the pores of the porous carbon material within the Si-C composite particles.
[0061] (Example 1) A lithium-ion secondary battery was fabricated using the following method.
[0062] [I] Fabrication of the positive electrode Lithium nickel cobalt manganese oxide (Li(Ni 0.9 Co 0.05 Mn 0.05 A cathode active material slurry was prepared by adding an appropriate amount of N-methyl-2-pyrrolidone to a solid component consisting of 97.5 parts by mass of O2, 1.5 parts by mass of polyvinylidene fluoride, and 1.0 part by mass of single-walled carbon nanotubes. Next, the cathode active material slurry was applied to a 12 μm thick aluminum foil, which serves as the cathode current collector, to achieve an initial charge capacity of 4.0 mAh / cm² per unit area. 2 After coating with an amount such that the desired result was obtained, the material was dried to obtain a positive electrode laminate. Next, using a roll press machine, the positive electrode laminate was processed so that the density of the positive electrode active material layer was 3.5 g / cm³. 3 The positive electrode was obtained by pressing it with a pressure such that it would result in a positive electrode.
[0063] [II] Fabrication of negative electrode active material Graphite powder and Si / C powder 1 were mixed to form the negative electrode active material of Example 1. The mixing ratio of graphite powder to Si / C powder 1 was 85:15 (by mass).
[0064] [III] Fabrication of the negative electrode A slurry of the negative electrode active material was prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of the negative electrode active material from Example 1, 0.1 parts by mass of single-walled carbon nanotubes (SWCNTs), and 3.0 parts by mass of lithium polyacrylate (PAA-Li). Next, the negative electrode active material slurry was applied to an 8 μm thick copper foil, which served as the negative electrode current collector, to achieve an initial charge capacity of 4.3 mAh / cm² per unit area. 2 After coating with an amount such that the following was achieved, the material was dried to obtain a negative electrode laminate. Next, using a roll press, the negative electrode laminate was processed so that the density of the negative electrode active material layer was 1.65 g / cm³. 3 The negative electrode was obtained by pressing with a pressure such that the following occurred.
[0065] [IV] Preparation of non-aqueous electrolyte The non-aqueous electrolyte was prepared by mixing an organic solvent with a supporting salt. The cyclic carbonate ethylene carbonate and the linear carbonate ethylmethyl carbonate were adjusted to a volume ratio of 3 / 7. Furthermore, lithium hexafluoride phosphate (LiPF6) (concentration: 1.2 mol / L) was used as the supporting salt, and fluoroethylene carbonate (concentration relative to the organic solvent: 6% by mass) was used as an additive.
[0066] [V] Fabrication of lithium-ion secondary batteries A positive electrode and a negative electrode were cut to 3cm x 3cm and placed opposite each other with a separator in between to create an electrode stack. A 10μm thick microporous polyethylene film coated with ceramic on both sides was used as the separator. Next, the electrode stack and a non-aqueous electrolyte were placed inside a laminate casing molded from a film mainly composed of aluminum. Positive electrode tabs and negative electrode tabs were connected to the negative electrode and positive electrode, respectively, and the casing was sealed to create a lithium-ion secondary battery. Here, one end of the positive electrode tab is connected to the positive electrode and the other end is led out of the casing, and one end of the negative electrode tab is connected to the negative electrode and the other end is led out of the casing.
[0067] (Examples 2-6 and Comparative Example 1) A negative electrode and a lithium ion secondary battery were respectively produced in the same manner as in Example 1, except that the type of Si / C powder, the blending ratio of graphite powder and Si / C powder, and the blending ratio of the negative electrode active material, binder, and conductive additive were respectively changed as shown in Table 1.
[0068] <STEM-HAADF Analysis> The negative electrode active material layer was taken out from the negative electrode of each of the Examples and Comparative Examples. Next, using STEM-HAADF (Scanning Transmission Electron Microscope-High-Angle Annular Dark Field method) (manufactured by JEOL Ltd., product name JEM-ARM200F Dual-X), the total area S of the Si-C composite particles was determined by the following method 1、 In the Si-C composite particles, the total area S2 of Si particles X having a projected area equivalent circle diameter of 10 nm or more and 200 nm or less, and the area ratio Y were measured. The results are shown in Table 1. (Method) Using 10 mg of the negative electrode active material layer, 10 Si-C composite particles were observed by STEM-HAADF (Scanning Transmission Electron Microscope-High-Angle Annular Dark Field method) under the conditions of a magnification of 1,000,000 times and an acceleration voltage of 200 kV, and STEM-HAADF images of each Si-C composite particle were respectively acquired. Next, using the image analysis software ImageJ (National Institutes of Health, USA) on the obtained STEM-HAADF images, the total area S1 of the Si-C composite particles, and the total area S2 of Si particles X having a projected area equivalent circle diameter of 10 nm or more and 200 nm or less calculated from the area value of each Si particle in the Si-C composite particles were respectively calculated. Next, the area ratio Y1 (=100×S2 / S1) was calculated from the obtained S1 and S2. The average value of the area ratios Y1 of the 10 Si-C composite particles was determined as the area ratio Y. Here, the total area S1 of the Si-C composite particles means the entire area of the observation range (Si-C composite particle portion) when one Si-C composite particle is observed, and the total area S2 of the Si particles X means the sum of the respective areas of each Si particle X included in the observation range.
[0069] <Capacity Retention Rate> Each lithium-ion secondary battery in the example and comparative example was placed in a constant temperature bath at 45°C and charged at 30mA. After the upper voltage limit reached 4.2V, it was charged at a constant voltage until the total charging time was 2.5 hours. Next, it was discharged at a constant current of 30mA until the lower voltage limit reached 2.5V. This charge-discharge cycle was repeated 500 times, and the ratio of the discharge capacity after 500 cycles to the discharge capacity after 1 cycle was calculated as the capacity retention rate (%). The results are shown in Table 1.
[0070] <Energy Density> For each example and comparative example of lithium-ion secondary battery, charging was performed at 7.2mA, and after the upper voltage limit reached 4.2V, charging was continued at a constant voltage until the total charging time was 12 hours. Next, the battery was discharged at a constant current of 7.2mA until the lower voltage limit reached 2.5V. Then, it was charged again under the same conditions, left in a 45°C constant temperature bath for 3 days, discharged again under the same conditions, and then charged and discharged one more time. During this process, the capacity and average voltage at the time of the final discharge were measured. Next, the thickness of the lithium-ion secondary battery was measured after the final discharge. Then, based on the above measurements, the electrode area of the electrode stack, the thickness of the laminate casing, the thickness of the negative electrode current collector, and the thickness of the positive electrode current collector, the cell-equivalent energy density (Wh / L) was calculated using the following formula. The results are shown in Table 1. (Energy density) = (Capacity at the end of discharge) × (Average voltage at the end of discharge) / (Electrode area of the electrode stack) / ((Thickness of lithium-ion secondary battery) - (Thickness of laminate casing) - (Thickness of positive electrode current collector) / 2 - (Thickness of negative electrode current collector) / 2)
[0071] [Table 1]
[0072] The raw materials for the lithium-ion secondary batteries in each example and comparative example are as follows.
[0073] <Negative electrode active material layer> (Negative electrode active material) • Graphite powder: A mixture of artificial graphite containing amorphous carbon on its surface and artificial graphite not containing amorphous carbon on its surface, in a 1:1 (mass ratio) mixture. • Median diameter D of artificial graphite containing amorphous carbon on its surface 50 :13.5μm, specific surface area: 1.5m 2 / g • Median diameter D of artificial graphite that does not contain amorphous carbon on its surface 50 :9.5μm, specific surface area: 1.8m 2 / g (Conductive additive) Single-walled carbon nanotubes (SWCNTs, aspect ratio: 2000, specific surface area: 1200 m²) 2 / g) (Binder) • Lithium polyacrylate (manufactured by Sumitomo Seika Co., Ltd., AquaCharge) [Explanation of Symbols]
[0074] 1 Cathode active material layer 2 Negative electrode active material layer 3 Positive electrode current collector 4 Negative electrode current collector 5 Separators 6. Exterior 7. Exterior 8 Negative Electrode Tabs 9 Positive Tab 10 Lithium-ion rechargeable batteries
Claims
1. A negative electrode comprising a negative electrode active material layer containing a negative electrode active material and a binder, The negative electrode active material comprises graphite powder and Si / C powder containing Si-C composite particles. A negative electrode having an area ratio Y of 25 area % or less, as measured by the method described below (Method 1). (Method 1) The Si-C composite particles in the negative electrode active material layer are observed using STEM-HAADF (scanning transmission electron microscope - high-angle scattering annular dark-field method) under conditions of a magnification of 1,000,000x and an acceleration voltage of 200 kV, and a STEM-HAADF image of the Si-C composite particles is obtained. Next, the total area S of the Si-C composite particles is determined from the STEM-HAADF image using image analysis software. 1 , and the total area S of Si particles X whose projected area circle equivalent diameter calculated from the area value of each Si particle in the Si-C composite particle is 10 nm or more and 200 nm or less. 2 Next, calculate the obtained S. 1 and S 2 From area ratio Y 1 (= 100 × S) 2 / S 1 Calculate the area ratio Y of any 10 Si-C composite particles. 1 Let the average value be the area ratio Y.
2. The negative electrode according to claim 1, wherein the content of the graphite powder in the negative electrode active material is 25.0 parts by mass or more and 99.0 parts by mass or less, when the total amount of the negative electrode active material is 100.0 parts by mass.
3. The negative electrode according to claim 1 or 2, wherein the content of the Si / C powder in the negative electrode active material is 1.0 part by mass or more and 75.0 parts by mass or less, when the total amount of the negative electrode active material is 100.0 parts by mass.
4. The median diameter D in the volume frequency particle size distribution of the graphite powder as measured by the laser diffraction scattering method 50 is 1.0 μm or more and 30.0 μm or less, the negative electrode according to any one of claims 1 to 3.
5. Median diameter D in the volume frequency particle size distribution of the Si / C powder obtained by laser diffraction scattering method. 50 The negative electrode according to any one of claims 1 to 4, wherein the diameter is 1.0 μm or more and 20.0 μm or less.
6. The negative electrode according to any one of claims 1 to 5, wherein the binder comprises a polycarboxylic acid polymer.
7. The negative electrode according to claim 6, wherein the polycarboxylic acid polymer includes an alkali metal salt of a polycarboxylic acid.
8. The negative electrode according to any one of claims 1 to 7, wherein the content of the binder in the negative electrode active material layer is 1.0 part by mass or more and 10.0 parts by mass or less when the total amount of the negative electrode active material layer is 100 parts by mass.
9. The negative electrode according to any one of claims 1 to 8, wherein the negative electrode active material layer further comprises a conductive additive.
10. The negative electrode according to claim 9, wherein the content of the conductive additive in the negative electrode active material layer is 0.01 parts by mass or more and 2 parts by mass or less when the total amount of the negative electrode active material layer is 100 parts by mass.
11. The negative electrode according to claim 9 or 10, wherein the conductive additive comprises a carbon material.
12. The negative electrode according to any one of claims 9 to 11, wherein the conductive additive comprises carbon nanotubes.
13. The density of the negative electrode active material layer is 0.70 g / cm³. 3 The negative electrode according to any one of claims 1 to 12.
14. A lithium-ion secondary battery comprising the negative electrode according to any one of claims 1 to 13.
15. A lithium-ion secondary battery according to claim 14, wherein the energy density is 725 Wh / L or more on a cell basis.
16. A lithium-ion secondary battery module comprising the lithium-ion secondary battery according to claim 14 or 15.
Citation Information
Patent Citations
Electroactive Materials for Metal-Ion Batteries
JP2023517052A